2008
DOI: 10.1124/jpet.107.131524
|View full text |Cite
|
Sign up to set email alerts
|

A Conservative, Single-Amino Acid Substitution in the Second Cytoplasmic Domain of the Human Serotonin2C Receptor Alters Both Ligand-Dependent and -Independent Receptor Signaling

Abstract: The post-transcriptional process of mRNA editing changes up to three amino acids in the second intracellular domain (i2) of the serotonin 2C (5-HT 2C ) receptor and alters some signaling characteristics of the receptor. Here, we report that the substitution of valine for isoleucine (I156V; 5-HT 2C-VNI ), which occurs naturally as a result of mRNA editing, alters both ligand-dependent and -independent signaling. Agonist functional selectivity at the 5-HT 2C-VNI receptor differed from the nonedited 5-HT 2C-INI r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Occurrence of adenosine-to-inosine editing at site A of 5-HT2C mRNA is known to generate a 5-HT2CR isoform with substitution of valine for isoleucine at a position 156 (5-HT2CR I156V ) within the putative second intracellular domain of the receptor. Recently, Berg et al 17) have demonstrated that a conservative change in one amino acid (I156V) of the 5-HT2CR produces profound changes in receptor function that differ depending on whether the receptor is unoccupied or occupied by agonist. They also suggest that phospholipase A2 (PL-A2) signaling of 5-HT2CR is influenced by this substitution (I156V) without affecting the phospholipase C signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of adenosine-to-inosine editing at site A of 5-HT2C mRNA is known to generate a 5-HT2CR isoform with substitution of valine for isoleucine at a position 156 (5-HT2CR I156V ) within the putative second intracellular domain of the receptor. Recently, Berg et al 17) have demonstrated that a conservative change in one amino acid (I156V) of the 5-HT2CR produces profound changes in receptor function that differ depending on whether the receptor is unoccupied or occupied by agonist. They also suggest that phospholipase A2 (PL-A2) signaling of 5-HT2CR is influenced by this substitution (I156V) without affecting the phospholipase C signaling.…”
Section: Discussionmentioning
confidence: 99%
“…RNA editing decreases binding affinity of agonists and alters some coupling, ligand-functional selectivity, and signaling characteristics of the receptor Niswender et al, 1999;Berg et al, 2008a;Werry et al, 2008a). Differentially edited receptors exhibit varying degrees of constitutive activity at G protein-dependent signaling, ranging from the highest for the nonedited 5-HT 2C-INI receptor to intermediate for partially edited isoforms and negligible for the fully edited 5-HT 2C-VGV receptor Niswender et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian cells (NIH3T3, CHO, COS-7, HEK293 or CV1), which stably or transiently transfected with nonedited or edited serotonin 5-HT 2C receptor isoforms, have been used as the cellular models for the studies of related signaling pathways and the modification of receptor function by RNA editing [14,15,18,24,25]. However, only a few serotonin receptor cell models of AD were utilized [11] and no RNA edited 5-HT 2C receptor isoforms cell model exists to provide appropriate cellular system to study the association between the RNA edited serotonin 5-HT 2C receptor isoforms and APP metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The partially edited receptor isoforms express valine, asparagine, and isoleucine (VNI), valine, asparagine, and valine (VNV), or valine, serine, and valine (VSV), whereas the fully edited isoforms express valine, glycine, and valine (VGV) (Fig. 1) [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%